The Amino Acid Metabolic and Carbohydrate Metabolic Pathway Play Important Roles during Salt-Stress Response in Tomato - Zhang, Zhi; Mao, Cuiyu; Shi, Zheng; Kou, Xiaohong (Frontiers in Plant Science, 2017)
Salt stress affects the plant quality, which affects the productivity of plants and the quality of water storage. In a recent study, we conducted the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) analysis and RNA-Seq, bioinformatics study methods, and detection of the key genes with qRT-PCR. Our findings suggested that the optimum salt treatment conditions are 200 mM and 19d for the identification of salt tolerance in tomato. Based on the RNA-Seq, we found 17 amino acid metabolic and 17 carbohydrate metabolic pathways enriched in the biological metabolism during the response to salt stress in tomato. We found 7 amino acid metabolic and 6 carbohydrate metabolic pathways that were significantly enriched in the adaption to salt stress. Moreover, we screened 17 and 19 key genes in 7 amino acid metabolic and 6 carbohydrate metabolic pathways respectively. We chose some of the key genes for verifying by qRT-PCR. The results showed that the expression of these genes was the same as that of RNA-seq. We found that these significant pathways and vital genes occupy an important roles in a whole process of adaptation to salt stress. These results provide valuable information, improve the ability to resist pressure, and improve the quality of the plant.